Causes and associated factors with male infertility among couples visiting infertility/andrologist clinics - Raghuwanshi, Pratibha Turiya; Kanwal , Merlin Raj (Journal of Drug Delivery and Therapeutics, 2025)
Introduction: Infertility is a global public health issue, affecting couples worldwide. The WHO defines infertility as the inability to conceive after one year of regular, unprotected intercourse. Male infertility accounts for 50% of cases and is influenced by various physiological, environmental, and lifestyle factors. This descriptive study aimed to identify the causes and associated factors of male infertility among couples visiting infertility/andrology clinics in Indore from 2016-2017. Methodology: An exploratory descriptive design was used, with 90 male participants selected through purposive sampling. Data were collected via structured questionnaires covering socio-demographic, personal, medical, surgical, and psychological aspects. Physiological and biochemical parameters were assessed to determine specific causes of infertility. Results: The common causes identified were azoospermia, oligospermia, asthenospermia, mixed pathology, and low semen volume. Tobacco use showed a significant association with male infertility (χ2 = 17.45, p < 0.05), while no significant associations were found with other factors such as age, occupation, or medical history. Participants often had a history of smoking or environmental pollutant exposure. Discussion: The study emphasizes the multifactorial nature of male infertility, highlighting the influence of physiological factors and lifestyle choices, particularly tobacco use. Comprehensive interventions addressing both medical and lifestyle factors are recommended for better fertility outcomes. Keywords: Male infertility, Azoospermia, Oligospermia, Asthenospermia. Mixed pathology, Less volume.